Fenton’s process for removal of resistant bacteria from unprotected aquifer samples - Singh, Visakha; Reddy, M. Kiranmai (Frontiers in Water, 2025)
This study investigated and analysed the presence and antibiotic resistance profiles of Enterobacter strains from municipal water supply and groundwater sources (open wells and handpumps) in a low-income neighbourhood of urban Visakhapatnam, India. Low-income neighbourhoods within the industrialised area of Gajuwaka were found to show high levels of groundwater contamination with multidrug-resistant bacterial strains. Two of these isolates were identified to be multidrug-resistant (MDR) strains, Enterobacter cloacae DSM 30054 (V1) and Enterobacter quasihormaechei WCHEs120003 (V2). The two isolates showed a similar profile with resistance towards penicillins, carbapenems, early and third-generation cephalosporins (such as cephalothin and ceftazidime, respectively), aztreonam, nitrofurantoin, and chloramphenicol. Susceptibility was noticed against cefepime (4th-generation cephalosporin), fluoroquinolones, and piperacillin-tazobactam. This profile suggests a combination of various intrinsic and acquired resistance mechanisms involving chromosomal AmpC β-lactamases and acquired resistance genes, including ESBLs and carbapenemases, potentially facilitated by porin loss. The isolates showcased high MAR index values above 0.5, indicating an environment with high resistance-inducing factors. Since higher levels of contamination were observed in the groundwater than in the municipality’s tap water samples, a type of advanced oxidation process (AOP) called Fenton’s reaction was evaluated for its efficacy in clearing the contamination from the groundwater samples of Visakhapatnam. Reduction in bacterial coverage levels on agar plates with different ratios of Fenton’s reaction regents was noticed during this experiment, going as high as 89.50% reduction (0.2 mM Fe2+ from ferrous ammonium sulphate, 0.5 mM H2O2, and pH 3). The findings of this study observed contamination of drinking water sources in vulnerable communities and highlighted the role of environmental water sources as reservoirs for resistance in Enterobacter spp. This investigation also provided an evaluation of the Fenton-based AOP as a viable technology for the remediation of contaminated groundwater in resource-limited settings of low-income neighbourhoods. There is a need for stringent monitoring of all water sources to maintain universal access to safe drinking water for every individual.